Comparison of efficacy and haemodynamic changes between endoflex with glide-rite styletted standard endotracheal tube in glidescope video larnygoscopy intubation. - Mohamad Zain, Zainiyah (2015)

(untitled)
The GlidescopeVideolarnygoscope has been widely used for intubation in recents years.Due to unique angulation of the blade,a dedicated stylet is provided ,utilized to facilitate intubation.The Endoflex endotracheal tube is a single lumen with in-built flexing mechanism and a friction lock that allows for easy articulation of its distal tip over a range of angles without the need for rigid stylet.The aim of this study was to evaluate between Endoflex with Glide-Rite styletted standard endotracheal tube in Glidescope video larnygoscopy intubation in term time for intubation,intubation attempts,intubation difficulty,hemodynamic changes and complications.This study was conducted from August 2013 till February 2014 involving a total number of 88 patients aged between 18 to 55 years old.The result showed mean insertion time to intubation with Endoflex is longer compared to Glide-Rite styletted standard endotracheal tube with p value <0.001 and also had higher fraction of second attempt with p:0.006 .Visual analogue score were higher in Endoflex with p:0.011. There were no statistically significant differences in term of haemodynamic changes and complication between both groups. In our study,we conclude that Endoflex was generally more difficult to insert as reflected by by longer intubation time,more intubation attempts, and higher intubation score.